Analisis Efisiensi Saluran Pemasaran Ikan Cakalang (Katsuwomus Pelamis) di Desa Dongkala Kecamatan Pasarwajo Kabupaten Buton - Safitri, Ririn; Saediman, Haji; Limi, Muhammad Aswar (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
The study is conducted to know marketing channel and efficient marketing channel Skipjack in Dongkala Village Pasarwajo Subdistrict Buton Regency. The research was carried out from May 2017 to August 2017. The determination of the sample is done by snowball sampling method that is searching data from a fisherman who reveals data as many as 30 fishermen and searches data from marketing agencies that reveal data as many as 16 people marketing agencies. Data obtained from questionnaires and direct interviews. The analysis used to answer the purpose of research that is descriptive quantitative analysis using marketing margin analysis dan fishermen’s share. Result of research indicates there are 3 marketing channel that used in Dongkala Village Pasarwajo Subdistrict Buton Regency that is (1) fishermen –district traders – end consumers, (2) fishermen – retailers – end consumers, (3) fishermen – end consumers. All marketing channels are considered efficient, but when viewed from the marketing margin and fishermen’s share, marketing channel III is considered the most efficient with a marketing margin of 0,00 % end fishermen’s share of 100 %.